Produção de antígenos de Leptospira interrogans em Pichia pastoris e avaliação do potencial imunoprotetor contra leptospirose - Hartwig, Daiane Drawanz (2010)
Leptospirosis is a serious infectious disease caused by pathogenic spirochetes of the genus Leptospira, it is classified as a zoonosis of worldwide distribution. This disease results morbidity and mortality in humans and animals, justifying the application of prophylactic strategies. Current vaccines against leptospirosis are composed of inactivated bacteria and do not stimulate cross-protection. Thus, there is need to develop a safe and effective vaccine. In this study, we used the outer membrane proteins LigANI e LipL32, because they have been identified as vaccinogens. These, in their recombinant form, are usually expressed in Escherichia coli and as subunit vaccines have shown variable efficacy. We describe in this work the use of Pichia pastoris as an alternative expression system. The genes ligANI and lipL32 were cloned into vector pPICZαB, which allowed the secretory expression of proteins in P. pastoris. The protein yield in this system was 276 mg/L for LigANI and 285 mg/L for LipL32. The recombinant proteins were glycosylated and remained antigenic. The immunoprotective potential was evaluated in the hamster model, challenged with virulent L. interrogans serovar Copenhageni. Both proteins induced high levels of antibodies (P < 0.001). The animals immunized with LigANI and LipL32 using aluminium hydroxide as adjuvant, showed no protection against challenge, but showed a significant increase in survival (P < 0.001). In conclusion, the yeast P. pastoris has proved an efficient heterologous expression system of LigANI and LipL32 L. interrogans proteins. The secreted and glycosylated LigANI protein may be used in the control of leptospirosis, although additional studies are needed.